A process warehouse based resource performance evaluation method for business processes improvement - Sohail, A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Existing studies on business process improvement (BPI) have widely focused on development of separate techniques for resource management and structural redesign of processes. In this study, we contend that the relationship of resource with task is not sufficiently understood. Particularly, business intelligence based approaches to BPI have not adequately explored this relationship. To understand this, we classify resources into human and non-human resources, because the two types of resources behave differently leaving different impact on process performance. Subsequently, a set of relationships between human resources, non-human resources and tasks (named suitability, preference and competence) are presented. However, only human resource's relationship with non-human resource/s (named preference) is presented in detail, as a resource preference model. The model bundled with the presented preference evaluation method guides users for evaluation of resources' preference. The applicability of the method is illustrated through a healthcare case study. Â© 2014 IEEE.